2013
DOI: 10.1097/igc.0b013e3182a57ff6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Anemia and Blood Transfusion on Patients With Stage III-IV Ovarian Cancer

Abstract: Our study is a retrospective analysis of the effects of anemia and transfusion on ovarian cancer. The rates of anemia in chemotherapy patients are higher than previously reported. Although maintaining average hemoglobin greater than 80 g/L during chemotherapy portends an improved overall survival, blood transfusion does not have any effect. The role of transfusion should therefore be limited to symptomatic patients while giving 1 unit at a time. Further prospective studies will be needed to confirm these resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 49 publications
(59 reference statements)
0
16
0
Order By: Relevance
“…Low hemoglobin is common in oncological diseases, including in lung (16,17), breast (17), gastric (18) and ovarian cancer (19). There is evidence for a correlation between hemoglobin levels and the prognosis of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Low hemoglobin is common in oncological diseases, including in lung (16,17), breast (17), gastric (18) and ovarian cancer (19). There is evidence for a correlation between hemoglobin levels and the prognosis of patients with NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[3, 4] Numerous studies have demonstrated that anemia is a prognostic indicator of poor clinical and oncologic outcomes. [510]…”
Section: Introductionmentioning
confidence: 99%
“…In this investigation, we demonstrate that implementation of standardized blood transfusion practices, an intraoperative hemostasis checklist, enhancedintraoperative fluid status communication, and evidence-based use of tranexamic acid was associated with reduced blood loss and red blood cell transfusion rates for patients undergoing laparotomy for ovarian or advanced endometrial cancer. This reduction is clinically important, given that perioperative blood transfusion carries well-described risks and negative outcomes (16, 25). While a bundled approach focused on reducing blood transfusion in gynecologic oncology patients has not been previously reported, our findings are consistent with those published in previous studies showing the efficacy of tranexamic acid and standardized blood transfusion guidelines (7, 13).…”
Section: Discussionmentioning
confidence: 99%